Enhancement of English Student Learning Results through Total Physical Response (TPR) Method - Wahyuni Sakka; Muhammad Aswad; Fajriani Fajriani (Universitas Sulawesi Barat, 2018)
The study was conducted in Madrasah Tsanawiah (MTs) Totolisi Sendana Majene Distric, West Sulawesi Province, this school was chosen purposively based on several considerations, namely: 1) the lack of number of English teachers, 2) the minimum number of learners is proportional to their interest in learning English, 3) the methods used by educators are less creative and innovative. Based on the issues raised in this study, the research entitled